2011
DOI: 10.1111/j.1365-2303.2011.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative squash cytology: accuracy and impact on immediate surgical management of central nervous system tumours

Abstract: Squash cytology is a rapid, reliable, simple technique for intraoperative consultation in neurosurgical practice with high overall accuracy. Causes causing an adverse impact on surgical management were rare and potential avoidable reasons for them were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 8 publications
1
35
0
2
Order By: Relevance
“…Cigarette smoking is an important risk factor for atherosclerotic vascular disease [3, 4]. Endothelial dysfunction occurs early in the pathogenesis of atherosclerosis [5, 6]. We have shown that stable reactive aldehydes present in cigarette smoke promote endothelial dysfunction by increasing the production of NADPH oxidase-derived reactive oxygen species (ROS) [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking is an important risk factor for atherosclerotic vascular disease [3, 4]. Endothelial dysfunction occurs early in the pathogenesis of atherosclerosis [5, 6]. We have shown that stable reactive aldehydes present in cigarette smoke promote endothelial dysfunction by increasing the production of NADPH oxidase-derived reactive oxygen species (ROS) [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…[8] [9] R-ICC by microwave-based method for intraoperative peritoneal washing cytology of pancreatic or biliary carcinoma was previously reported [10]. Recently, the usefulness of R-ICC of cytokeratin in touch print of sentinel lymph nodes for evaluating metastasis of breast cancer has been reported [11] [12].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the examination should be accurate, fast, and allow tissue preservation for further study in paraffin [4-6]. The most commonly used techniques are squash and frozen section (FS) [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, FS is more applicable in cases in which performing the squash technique can be difficult, such as lesions that need better evaluation of the architectural aspects and those with firm consistency [6, 7]. …”
Section: Introductionmentioning
confidence: 99%